Improving the Fontan: Pre-surgical planning using four dimensional (4D) flow, bio-mechanical modeling and three dimensional (3D) printing. (December 2016) - Hegde, Sanjeet; Hsiao, Albert
Abstract: While early and intermediate results of Fontan palliation have greatly improved the survival and quality of life of patients with single ventricle physiology, late complications remain concerning, and leave room for further improvement. In addition to recent advances in surgical techniques and post-operative care, advances in Medical Imaging and related technologies can further improve pre-surgical planning and post-operative management of these complex patients. Novel technologies including advanced MRI, computer aided design, three-dimensional printing, Virtual Surgery and Computational Fluid Dynamics may provide better patient-specific surgical plans, and continue to improve long-term outcomes.